Growth Rate Determination of Listeria monocytogenes in Ready-To-Eat Fish Products Under Different Storage Conditions for Possible Shelf-Life Extension - Paolo Cipriani; Elena Dalzini; Elena Cosciani-Cunico; Muhammad-Ehtesham Abdul; Paola Monastero; Daniela Merigo; Stefania Ducoli; Alessandro Norton; Marina-Nadia Losio; Enrico Pavoni (Foods, 2025)
An increasing trend among food business operators (FBOs) to extend the shelf life of Ready-To-Eat (RTE) fish products over 5 days, the duration usually assigned to this kind of product, has been observed recently. In this study, three independent challenge tests (food artificial contamination) were performed on tuna fillet, marinated salmon tartare, and cubed salmon, with the aim of calculating the maximum growth rate (Vmax) of Listeria monocytogenes and estimating the time required to reach the legal limit of 2 log CFU/g, as established by European Regulation 2073/2005. The pathogen counts were fitted by the model of Baranyi and Roberts to calculate the Vmax, which were 0.041, 0.020, and 0.039 log CFU/g·h−1, respectively, for the tuna fillet, marinated salmon tartare, and cubed salmon at 10 °C. These results can help FBOs in assigning the correct shelf life based on hygienic practices during the process, product characteristics, and storage conditions. The time to reach the legal limit greatly depends on the starting concentration of the pathogen and on the storage temperature. The challenges for FBOs and the health authorities include reducing the contamination of L. monocytogenes, controlling the retail temperatures, and implementing the analytical tests for quick responses.